Foundations of psychological testing a practical approach - Miller, Leslie A.; McIntire, Sandra A. 1944-.; Lovler, Robert L.; McIntire, Sandra A. 1944- (Thousand Oaks, Calif. SAGE, 2011)
A straightforward and clear introduction to the basics of psychological testing as well as to psychometrics and statistics for students new to the field. The authors focus on relating core ideas to practical situations that students will recognize and relate to.
What are psychological tests? -- Why is psychological testing important? -- Is there a right or wrong way to use psychological tests? -- How does computerized testing work? -- How do test users interpret test scores? -- What is test reliability? -- How do we gather evidence of validity based on the content of a test? -- How do we gather evidence of validity based on a test?s relationships with external criteria? -- How do we gather evidence of validity based on a test?s relationship with constructs?
Previous ed. entered under: McIntire, Sandra A.
Keywords: Psychological tests -- Textbooks